Integrasi Pendidikan AlQuran dan Budaya Alam Minangkabau dalam Mata Pelajaran PAI di SMA Negeri 9 Padang - Anjeli, Mardawila Adha; Kustati, Martin; Gusmirawati, Gusmirawati (Lembaga Yasin AlSys, 2024)
This research was motivated by wanting to know information about the implementation of schools integrating Al-Quran education and Minangkabau Natural Culture at SMA Negeri 9 Padang. The aim of this research is to determine the planning, implementation, results and obstacles to the integration of Al-Quran Education and Minangkabau Natural Culture in PAI subjects at SMA Negeri 9 Padang. The type of research used is field research using descriptive methods and data collection techniques based on observation, interviews and documentation. The data processing technique is carried out by creating an interview instrument in the form of questions asked to the informant. Data sources are school principals, PAI teachers and students of SMA Negeri 9 Padang. The results of the research are that the integration of Al-Quran Education and Minangkabau Natural Culture in PAI subjects at SMA Negeri 9 Padang is carried out starting with planning which is carried out in 2 forms, firstly, intra-curricular, which is linking Al-Quran verses and Minangkabau cultural values into learning materials, secondly, extra-curricular, namely programs rohis, Minang corners, Minang clothing, and end of school year programs. Meanwhile, the implementation is held at school, both inside and outside the classroom. The results of implementing this integration are well implemented and can increase students' knowledge regarding the values of the Alquran and Minangkabau cultural values. The obstacles are lack of time and lack of books for students to use, teachers' lack of knowledge in mastering Minangkabau philosophy.